Analysis of Consumer Satisfaction Toward the Quality of Moringa Leaf Noodles (Migreen) Product by PT Liefde Herb Nusantara - Alda Bintang Alvanda; Rika Nalinda; Siwitri Munambar (Majapahit Journal of Islamic Finance and Management, 2026)
This study aimed to analyze consumer satisfaction toward the quality of Moringa leaf noodles (MiGreen) with Chicken Onion flavor produced by PT Liefde Herb Nusantara using the Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), and GAP Analysis methods. The research was conducted in the Special Region of Yogyakarta from November 2025 to April 2026 using a quantitative descriptive approach with an accidental sampling technique involving 50 respondents. The results showed that no attributes were included in Quadrant I, indicating that the attributes considered important by consumers generally demonstrated good performance. The Customer Satisfaction Index (CSI) value of 79.49% indicated that consumers were satisfied with the product, while the GAP Analysis showed a total GAP value of -2.78 and an average GAP value of -0.15. These results indicate that the product performance was slightly below consumer expectations; however, the gap was relatively small, meaning that the product was still well accepted by consumers. Therefore, the company needs to maintain product quality and continuously evaluate product attributes to improve consumer satisfaction.